A filosofia da imanência e a arte do skateboard - Torquato, Douglas de Melo Ferreira (2021)
The research appears circulating in the streets and “spots” of Uberlândia, multiplies in infinite nuances, is in the midst of different situations and relationships, is in a “board” in our city and region, composing an intense exchange of signs with different characters and with the city itself. Inspired by music, by philosophy, by contact with nature, by social life, by the local “crews”: SkateVandalCrew, Platinum Skateboard, Marginália and others, and by certain outside crews, such as the Flanantes crew. We have as objects of this research the texts of Leonardo Brandão and Giancarlo Machado on the rise of skateboarding, street skateboarding in São Paulo and the concepts coming from other authors, like Foucault and Deleuze, worked by those, such as city, heterotopia, rhizome, etc. Also some texts sent by Gibus de Soultrait, founder of the French magazine Surf Session, and Surfer Journel, which dialogue with Deleuze’s philosophy. Our text extends in search of multiplying and analyzing the senses and meanings of the practice of street skating (streetskate), and not just understanding it as a modality of Olympic sport. Through fieldwork and ethnographic recording (carried out before the pandemic), it is intended to show the multiplicity of athletes, artists, personalities, philosophies and discourses around this sport and its infinite expansion, its networks, connections, continuities and discontinuities. We make use of interviews, audiovisual production, the registration of championships, and through this we expose the most varied aspects around this sports practice. We research our city, new ways of appropriating it, we research its high performance athletes and the human being behind it, and those who make up a more playful, or artistic view of skateboard and its importance, its ethos. We investigated a vast collection of academic works on skateboarding, however, we propose a research focused on concepts and contents arising from the works of Gilles Deleuze and Espinosa, as well as Guattari, Mbembe, Foucault, and academic skaters such as Leonardo Brandão, Giancarlo Machado, Soultrait Gibus etc.